The Implications of Organizational Slack-Resources Heterogeneity toward CSR Expenditures - Kadek Weda Noveadjani Tista; Aulia Fuad Rahman; Arum Prastiwi (Journal of Accounting and Investment, 2021)
Research aims: This study aims to prove the alleged effect of organizational resource slack on corporate social responsibilities (CSR) expenditures. The types of organizational resource slack examined in this study were financial slack, human resource slack, and innovational slack. This research was conducted in the mining sector and basic and chemical industries listed on the Indonesia Stock Exchange during 2015-2019.Design/Methodology/Approach: Non-probability sampling technique with purposive sampling method was as the sampling method. It consisted of 13 companies with a total of 54 samples of observations. Hypothesis testing used multiple linear regression.Research findings: The results showed that financial slack had a negative effect on CSR expenditures. It supports agency theory used as a theoretical basis regarding management's tendency to manage slack over organizational resources. However, this study could not show the effect of human resource slack and innovational slack on CSR expenditures.Theoretical contribution/Originality: This study's results constitute empirical evidence related to agency theory explaining the effect of financial slack on CSR expenditures.Practitioner/Policy implication: This study’s results can illustrate the management’s tendency to allocate funds for CSR by considering the slack of various types of organizational resources. Improvements related to the implementation of Law No. 40 of 2007 about the responsibility of limited liability companies to carry out social and environmental responsibility also need to be concerned by the regulator.Research Limitation/Implication: The limitations in this study that can be considered for future research are related to very limited research data for certain variables. The data’s availability related to CSR costs and research and development costs included in the annual report is very limited, so the number of samples processed was limited.